Staff’s acceptability of non-pharmacological and pharmacological interventions for behavioral disturbances in nursing homes in Iceland - Tara Ósk Ólafsdóttir 1997- (2022)
This study was based on a Bakers and LeBlanc’s (2011) study which looked at three different treatments for behavioral problems in long term care settings; (1) Communication Treatment, (2) Light and Sensory Treatment and (3) Medication Treatment. This study explored staff’s acceptability of both non-pharmacological and pharmacological interventions for behavioral disturbances in individuals with neurocognitive disorders that are in Nursing homes in Iceland. Participants were recruted with an online recruting convenience sampling method. A total of 112 individuals answered the questionnaire. Findings revealed that there is little difference between these three treatments. However, staff members found the Communication Treatment to be the most frequently most acceptable, while Light and Sensory Treatment was found to be the least frequently most acceptable. The Medication Treatment scored the highest in terms of the staff’s belief that it would cause the most discomfort for the patient. This study depicts a variety of potentially beneficial interventions in geriatric care that should not be underestimated and have the potential to serve as important therapeutic measures for both staff and patients. Keywords: neurocognitive disorders, alzheimer, dementia, geriatric care, acceptability, medication treatment, communication treatment, light and sensory treatment Þessi rannsókn er byggð á rannsókn Baker og LeBlanc (2011) sem rannsökuðu muninn á þremur mismuanndi meðferðum við hegðunarvandamálum í langtímaumönnun sem eru; (1) Samskiptameðferð, (2) Ljósa og Skynmeðferð og (3) Lyfjameðferð. Í rannsókninni var mat starfsfólks á lyfjameðferð og meðferð án lyfja við hegðunarvandamálum hjá einstaklingum með taugvitræna sjúkdóma sem eru á hjúkrunarheimilum á Íslandi skoðað. Þátttakendum var safnað með aðgengisúrtaki á netinu. Alls svöruðu 112 einstaklingar spurningalistanum. Niðustöður sýndu að mörgu leiti lítinn mun á meðferðunum þremur. Samt sem áður fannst starfsfólki Samskiptameðferðin oftast ásættanlegust en ljósa og ...